Kepemimpinan kepala madrasah dalam meningkatkan kinerja guru MA al ikhlas Pemetung Basuki - Zainur Rohman; Nurul Hidayati Murtafiah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Improving the quality of education in madrasah is a component that significantly determines the success of leadership. Madrasah leaders play a strategic role in improving teacher activity. This research aims to find out how madrasah management can improve the performance of MA Al Ikhlas Pemetung Basuki teachers. In this study, qualitative research methods were used. Data collection methods are observation, interview, and documentation. Data analysis includes data collection, data provision, and total pictures. The results showed that the leadership of the head of MA Al Ikhlas Pemetung Basuki has carried out leadership well, including in terms of influencing subordinates with communication to achieve goals, giving orders or tasks, motivating and coordinating teachers in realizing all plans to achieve the vision and mission of the madrasah and creating a sense of confidence and support among subordinates. This has a significant impact on improving teacher performance at MA Al Ikhlas Pemetung Basuki. However, it cannot be denied that the performance of MA Al Ikhlas Pemetung Basuki teachers still needs to be maximized